Development history of the “eco-city” concept and the last tendencies (Journal of Geography and Environmental Management, 2020)
At the beginning of the new millennium, a term appeared in literary sources explaining the desire to strengthen urban sustainability. Currently, this new phenomenon - an eco-city - has reached its height. The significant role of the eco-city is in solving such environmental problems as global warming, climate change and accelerated urbanization of the cities. That is, he began to become the focus of the mayors in their policies. The purpose of this article is to reveal the essence of the concept of “eco-city”. The article is devoted to the review of the most famous eco-cities around the world, as well as the definition of the same significant terms of the process of urban sustainability as “sustainable city”, “smart city”. This article uses the method of reviewing literary sources, a comprehensive analysis of the statistical data of scientists who dealt with this issue. As a result, it turned out: the phases of development of the concept of “eco-city”, and the types of ecocities themselves, which are also the types of their implementation. According to these parameters, this article presents descriptions of 79 eco-cities. The significance of this work lies in determining the similarities and differences between the projects of eco-cities in the world and the eco-model of a city in Japan.
Keywords: eco-city, urbanization, sustainability, sustainable city, smart city.